Rencana Pengembangan Desa Banaran sebagai Desa Wisata - Larasati, Stephani Rangga (Jurnal Atma Inovasia, 2021)
Abstract —  Peope service are required activities that become real steps for students in realizing their participation in a community. This program aims to create good relations between people of Banaran Village and Atma Jaya University in Yogyakarta, help increase the development of the potential of Banaran Village, and help preserve and market the typical arts of Banaran Village. Banaran Village has a lot of potential that can be explored and utilized for the welfare and progress of its community. These potentials incule Trisik Beach, Laguna, Turtle Conservation, Shrimp Ponds, Trisik Festival and Reog. In addition, this village has fertile soil so that it has the potential for ornamental plant business. This method of implementing people service program is by collecting data, analyzing potential, and compiling development plans in the form of designs, books, and videos. The implementations of people service is manisfested in the form of planning for Banaran Village to become tourist village in the form of tourism village designs, village potential e-books, and pocket book on ornamental plants.Keywords — People Service, Village Potential, Tourism Village, Banaran Village. Abstrak— Program pengabdian masyarakat merupakan langkah nyata mahasiswa dalam mewujudkan peran sertanya di tengah masyarakat. Program pengabdian masyarakat ini bertujuan untuk menciptakan hubungan baik antara masyarakat Desa Banaran dengan Universitas Atma Jaya Yogyakarta, membantu meningkatkan pengembangan potensi yang dimiliki Desa Banaran, serta membantu melestarikan dan memasarkan kesenian khas Desa Banaran. Desa Banaran memiliki banyak potensi yang dapat digali dan dimanfaatkan untuk kesejahteraan dan kemajuan masyarakatnya. Potensi tersebut antara lain Pantai Trisik, Laguna, Konservasi Penyu, Tambak Udang, Trisik Festival dan Reog. Selain itu, desa ini memiliki tanah yang subur sehingga berpotensi untuk usaha tanaman hias. Metode pelaksanaan program pengabdian ini dengan pengumpulan data, analisis potensi, dan penyusunan rencana pembangunan dalam bentuk desain, buku, dan video. Pelaksanaan pengabdian masyarakat diwujudkan dengan bentuk perencanaan desa Banaran menjadi desa wisata berupa desain desa wisata, e-book potensi desa, dan buku saku tentang tanaman hias.Kata Kunci— Pengabdian masyarakat, Potensi Desa, Desa Wisata, Desa Banaran.